Perspectives: Opportunities to improve research on climate change in forestry - Hakamada, Rodrigo; Santos, Lorena Paulina; Bandeira, Sara; Ramos, Rosilvam; Gonçalves, Gardênia [UNESP] (Elsevier, 2023)
This article explores the extent to which research in forestry is directly related to the issue of climate change. The study conducted two surveys, one analyzing 5, 210 theses from Brazilian forestry-related postgraduate programs between 2013 and 2022, and another examining 2228 articles published in ten forestry journals in 2022. We classified the extent of a focus on climate change in four classes: strong focus, relevant focus, using it as a context and not considered. Given the pervasive impacts of changing climates, we found a small representation of the topic within the theses with only 2% with a strong focus, 2% of relevant focus and 5% mentioned climate change as a contextual factor but provided no clear connections or inferences about climate change and forests. The focus on climate change was developed better in the forest journals. Almost one-third at least justified their projects based on connections to climate change, and 14% directly studied climate change and its impacts. Six percent of the papers with a direct focus on climate change also incorporated climate change effects into their experimental designs. We propose three key opportunities for improve the science about climate change related directly with forestry. Firstly, an opportunity is related with the writing of papers by itself, where articles might have substantive connections and insights connected with the core theme of the research. Secondly, taking Brazil as an example, there should have an increment in the number of graduate students working directly with the theme of climate change given its relevance. Lastly, we identified an opportunity for a more balanced science in the distinct types of forests. Tropical forest represents 45% of the forests worldwide but comprises only 14% of studies in our sample. By addressing these opportunities, we will not only benefit the forests but also contribute to a more sustainable and climate-resilient future for both forests and communities.
Keywords: Climatic change; Forest science; Forestry research; Global change; Increasing temperature